Absorption measurements of colored dissolved organic matter (cDOM) in Pohjanpitäjänlahti bay in May 2021 - Janina Pykäri (PANGAEA, 2022)
Water samples were collected from Pohjanpitäjänlahti bay in May 2021 from four stations along a coastal salinity gradient. Absorption coefficients at wavelengths 200-800 nm were measured for colored dissolved organic matter (CDOM) analyses from the water samples. The samples were collected 8 times straight to plastic bottles from a small boat. The data was collected to a thesis funded by Walter and Andreé de Nottbeck Foundation.
In: Pykäri, J (2022): Light attenuation data set along a coastal salinity gradient in Pohjanpitäjänlahti bay in May 2021 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.947091